(untitled) (Fisioterapia e Pesquisa, 2008)
The relationship between temporomandibular joint disorders (TMD) and different kinds of headaches is still not well understood, though headache is probably the most common symptom of TMD. The aim of this study was to correlate headache with Fonseca's TMD clinical index. A total of 160 university students aged 18 to 36 years old were selected, half women, half men. Two questionnaires were applied to them: the Fonseca clinical questionnaire and one on headache. Data were statistically analysed and significance level set at p